Synthesis, Characterization and Bioactivity Study of Bidentate NS Schiff Base of S-Benzyl Dithiocarbazate and its Zn(II) and Pd(II) Complexes - Islam, Md. Hasibul; Sheikh, Md. Chanmiya; Miyatake, Ryuta; Zahan, Ronok; Islam, Md. Al-Amin-Al-Azadul (Asian Journal of Chemistry, 2020)
The bis-chelated four coordinate complexes (ML2, L = deprotonated ligand) of Zn(II) and Pd(II) ions were synthesized, derived from a new bidentate NS Schiff base called S-benzyl-β-N-(4- hydroxy-3-nitrophenyl)methylene dithiocarbazate (HL) which is the condensation product of S-benzyl dithiocarbazate (SBDTC) with 4-hydroxy-3-nitrobenzaldehyde. The synthesized ligand and complexes were characterized using conventional techniques like NMR, UV-visible, IR, mass spectroscopic techniques, magnetic susceptibility measurement and molar conductance. A single crystal X-ray crystallography data approved the proposed crystal structure of the ligand. Both in solid and solution phase, the ligand continues to exist in its thione tautomeric form. The chelates were formed by the reaction of ligand with the metal ions through the ligand azomethine nitrogen atom and the deprotonated thiolate sulfur anion. Magnetic susceptibility and electronic spectroscopic data suggested to have a tetrahedral geometry for ZnL2 complex whereas a square planar structure for PdL2 complex. The analgesic and anti-inflammatory bioactivity were assayed on both the ligand and its complexes by tail flick and carrageenan induced paw edema test. The ligand at the dose of 10 mg/kg, produced a significant (***p < 0.001) increase in pain threshold in tail flick methods when compared to control but in case of complexes, it showed moderate activity. At the same dose, the ligand and complexes significantly (***p < 0.001) reduced paw edema when compared to the control. Altogether, these results suggest that ligand and its complexes could be used as a potent anti- inflammatory agent.